Protective Effects of Curcumin and Broccoli Seed Extract Against Age-Related Bone Loss in Mice. (29th May 2020) - Li, Jing; Zhang, Dong; Ren, Yiping; Qiao, Zhongdong; Stevenson, Doug; Bartlett, Mark
Abstract: Objectives: Age-related bone loss occurs in both men and women, and is the leading cause of elderly disability. An age-related bone loss model was established in mice to investigate the protective effects of curcumin and broccoli seed extract. Methods: 20 young (6-month-old) male C57BL/6 J mice after administration with vehicle once daily were sacrificed at four time points: day 0, 30, 60 and 90. 8 out of the 109 aged (18-month-old) male C57BL/6 J mice were sacrificed at the beginning and used as control. The rest of these aged mice were then randomly divided into four groups: one group served as control (vehicle), the other three groups were administrated with curcumin (CMN) and/or broccoli seed extract (BSE) by oral gavage. Mice in each group were sacrificed at four time points: day 0, 30, 60 and 90. L2 vertebrae of mice were fixed with paraformaldehyde and scanned with a Scanco Medical μCT40 scanner. Quantitative analyses of bone volume (BV), tissue volume (TV), trabecular number (Tb.N), trabecular thickness (Tb.Th) and trabecular spacing (Tb.Sp) were performed with the Scanco Medical's software. Results: BV/TV of the young mice group were significantly higher compared to the aged mice group at all four time points. Similarly, Tb.N and Tb.Th were also higher in the young mice group compared to the aged mice group. In contrast, Tb.Sp was lower in the young mice group. When comparing different groups in the aged mice, we found that mice administered with CMN had a higher BV/TV value compared to the mice in the control group at all three time points. Such a difference is significant by day 30. The mice administered with combined CMN and BSE also showed significant increase in BV/TV on day 30. For Tb.N, both mice administered with either CMN or BSE had higher values at all three time points. But no obvious difference in Tb.N was found for mice administered with combined CMN and BSE. For Tb.Th, both mice administered with CMN and with combined CMN and BSE had higher values compared to the control. For Tb.Sp, both mice administered with either CMN or BSE had lower values compared to the control. Conclusions: This study showed that curcumin could slow down bone loss in the mouse model. There is no obvious positive effect with broccoli seed extract or with curcumin and broccoli seed extract combined. The curcumin used in this study may shed light on the alleviation of bone loss in humans. Funding Sources: Nu Skin Enterprises.